Recent advances in processing, morphological evolution and applications of bismuth sodium titanate nanoceramics - Subramani Supriya (Open Ceramics, 2024)
Nanostructured hybrid functional perovskite materials are an exciting domain of electroceramic materials and have created attention among researchers due to the coexistence of multiple properties like piezo and ferroelectricity. It offers a broad range of applications in optics and electronics technology. One of its kinds, bismuth sodium titanate (Bi0·5Na0·5TiO3-BNT) nanomaterials, possesses an integral and significant role in advanced electronic industries. This article aims to systemize the deliberation related to the development of bismuth sodium titanate-based nanomaterials, including the study of nanomaterial morphology mechanism, fabrication methods, crystal structure, and its role in many other novel applications. This work focuses on analyzing behavior based on synthesis methods, the proposed approaches for optimizing morphology, and current challenges. Challenges and opportunities connected with the BNT nanomaterials are elaborated. This study could motivate young researchers to study and develop novel BNT-based nanomaterials so that we could get the best out of the research.